An Information-Based Nursing Quality Evaluation Model of Daily PICC Work in Outpatient Clinics. (21st July 2022) - Yi, Qingmei; Li, Xi; Chen, Tingting; Li, Zhiguo; Cao, Xiaohong; Gu, Wei
Abstract : Our purpose of this study was to analyze the application value of the information-based nursing quality evaluation model in improving the daily work quality of the PICC room in the outpatient department. From January 2020 to December 2020, 465 patients who received PICC treatment were selected as the research objects and divided into the observation group (265 cases, July 2020–December 2020, information-based nursing quality evaluation model after implementation) and the control group (200 cases, January 2020–June 2020, before the implementation of the information-based nursing quality assessment model). Compared with the control group, the children and their families in the observation group had higher PICC health knowledge and compliance scores, longer mean time for catheter placement, lower overall complication rate, and higher overall satisfaction rate after the intervention. The information-based nursing quality evaluation model can improve the daily work quality of the PICC room in the outpatient clinic, improve the clinical efficacy of PICC in patients, and reduce the incidence of complications such as catheter shedding. It is worthy of clinical application.